Optimization of serum preparation in Vero cell culture using a statistical approach - Ahmad Nor, Yusilawati; Nuhu Jaafar, Jaafar; Mel, Maizirwan (Universiti Malaysia Sabah, 2009)
Serum is a vital supplement in animal cell culture. Serum used in animal cell culture is from bovine source marketed by different companies, and somewhat expensive. The aims of this work were serum treatment and screening for the best serum concentration for Vero cell culture using STATISTICA software. The best result obtained from the software was used to compare with different commercial serum (GIBCOTM and PAA). Local serum was prepared first by aseptically collecting 500ml whole blood from disease free cattle using 50ml anticoagulant free centrifuge tubes. Whole blood was centrifuged to separate serum and blood cells. Serum collected was treated with ultraviolet radiation and heat inactivated for 30min at 56oC. Vero cells were cultured in 25cm2 T flasks with an initial cell seeding of 4.2 x 105 cells/ml. Results obtained showed that locally made serum is comparable in terms of maximum viable cell numbers (8.0 x 105 cells/ml) compared to commercial bovine serum (8.5x 105 cell/ml and 6.78x105 cell/ml) for GIBCO and PAA respectively after four days. From the study, locally prepared serum can be substituted to the commercial sera for Vero cell culture.